Sort by

- Relevance
- |Time

**k**^2 - 3k = 28**k**^2 - 3k - 28 = 0 (**k**- 7)(**k**+ 4) = 0**k**= -4, 7 and if you're asked to find x:**k**= -4: -4 = (x + 3)/(x - 4) -4(x - 4) = x + 3 -4x + 16 = x + 3 16 - 3 = x...2 Answers · Science & Mathematics · 18/08/2019

...e^(kx) - e^(-kx) ] / [ e^(3x) + e^(-3x) ] When x is large and assume

**k**>= 0 sinh(kx) / cosh(3x) ≈ e^(kx) / e^(3x) = e^(x(**k**- 3)) For sinh(kx...1 Answers · Science & Mathematics · 21/02/2019

**K**-pop is a dance style based off of basic hip hop and street jazz dance.... That is why you would be hard pressed to find**k**-pop classes anywhere. What you want to learn is basic dance ...1 Answers · Arts & Humanities · 21/05/2019

If 2x - 3y =

**k**, then 2x =**k**+ 3y, so x = 0.5k + 1.5y The circle is: (x - 3...0.25k^2 - 3k - 15) If the line is tangent to the circle, then**k**is real and there is only one possible solution for y, so the...1 Answers · Education & Reference · 03/02/2019

... SOLUTION: I like to use this notation: C(n,

**k**) = n! / [(n -**k**)!**k**!] That would mean: C(n, n -**k**) = n! / [(n...;--> {A, B, C} So C(n,**k**) = C(n, n-**k**)6 Answers · Science & Mathematics · 12/09/2019

Replace x with

**k**and y with 2 in x + 2y = 5:**k**+ 2(2) = 5**k**= 5 - 4**k**= 14 Answers · Science & Mathematics · 25/02/2019

(0.0015/0.03)*10^(m-

**k**) = 5 * 10^7 => (15/300)*10^(m-**k**) = 5*10^7 => 0.05*10^(m-**k**) = 5*10^7 => 10^(m-**k**) = 10^9 => m-**k**= 94 Answers · Science & Mathematics · 10/02/2019

For a) and b)

**K**= Kp = 7.04/3.45² = 0.591 (to 3 sig. fig.) The answer is...2y Equilibrium (atm): _ 1.57 - y ___ 1.57 - y _______ 2y At equilibrium:**K**= [B]² / ([C] [D]) 0.591 = (2y)² / (1.57 - y...1 Answers · Science & Mathematics · 23/02/2019

-365.05 F is 52.57

**K**-365.10 F is 52.54**K**<== this is ...2 Answers · Science & Mathematics · 11/07/2019

...question. Notice that the question says, "for what *values* of

**k**..." You did what most people know to do which is to use the...3 Answers · Science & Mathematics · 01/11/2019